Komunikasi untuk Pemeliharaan Hubungan Pertemanan antara “Gamers Online” - Basir, Rafi Usman; Naryoso, Agus (Interaksi Online, 2022)
The rapid development of online games and technology in Indonesia has created a virtual community. The virtual community (cyberspace) is a medium or place for individuals to seek information or interact with other individuals who have never met online before. This ongoing interaction can be done both personally and in groups, because basically humans cannot live without other people (social beings). Virtual community is a new concept in society where all interactions are carried out through the virtual world and without meeting face to face. The purpose of this study is to determine the process of maintaining friendships in virtual communities, as well as to find out how individuals who are members of virtual communities can avoid or overcome conflicts that arise in friendships in the virtual world. This study uses a qualitative method that refers to the interpretive paradigm with a phenomenological approach. The theory used in this research is relationship maintenance theory. The technique used in this study uses in-depth interviews with individual subjects who are members of the online gaming community, who are over 18 years of age and have joined the virtual community for more than 2 years. The results of the study reveal that individuals in virtual communities cannot feel intimate closeness with other friends because interactions carried out in virtual communities do not have non-verbal communication and physical contact. However, individuals still have a commitment to maintain friendly relations with virtual groups because they have the same goal, namely playing online games, virtual groups can be used as a means of interacting without being limited by geography. In addition, another reason individuals join and maintain friendly relations with other individuals in virtual communities is also because it can meet the information needs and social needs of all individuals who are members of it.